Iodine–Ethanol Surface Passivation for Measurement of Millisecond Carrier Lifetimes in Silicon Wafers with Different Crystallographic Orientations. Issue 17 (16th July 2019) - Al-Amin, Mohammad; Grant, Nicholas E.; Pointon, Alex I.; Murphy, John D.
Abstract : To improve silicon device fabrication processes, it is necessary to monitor bulk minority carrier lifetimes accurately, and this requires surface recombination to be well controlled and, ideally, minimized. Good surface passivation can result from thermal oxidation or by deposition of dielectrics (e.g., Al2 O3, SiN x, and amorphous Si), but these forms of passivation can modify the lifetime of the material under investigation. Various schemes can passivate surfaces on a temporary basis without modifying the bulk, and, in this article, the virtues of the iodine–ethanol (I–E) temporary surface passivation scheme are explored. A procedure for preparing the wafer surfaces prior to passivation is developed. For the optimized pretreatment, a series of experiments on 3–5 Ω cm float‐zone wafers cut from the same ingot with different thicknesses is conducted. This enables the material's bulk lifetime to be measured at 10 15  cm −3 injection as 46 ms, with the surface recombination velocity being 6.5 ± 0.3 cm s −1 . I–E passivation is then compared to a recently developed superacid‐derived temporary passivation scheme. Although the latter is superior on (100)‐orientation substrates, I–E performs much better on (111)‐orientation substrates, making it a better choice for (111)‐orientation wafers, such as those used for power devices. Abstract : Excellent passivation of silicon surfaces is achieved via optimization of an iodine–ethanol (I–E) scheme. A robust method based on samples with different thicknesses cut from the same float‐zone ingot is used to determine a lowest surface recombination velocity of 4.4 cm s −1 for (100)‐orientation silicon. I–E is demonstrated to be superior to superacid‐derived passivation for (111)‐orientation silicon surfaces.